Halal branding architecture on social sustainability among personal care and cosmetics customers: the moderating role of social media. - Ramdzan Ali, Al Amirul Eimer (2019)
Organizations, retailers, entrepreneurs have leveraged on Branding Architecture with the hope to sustain its business operations and at the same time, maintaining the social welfare of its customers These strategies might not be successful when they are applied in Muslim countries In addition, business operators are facing difficulties to choose the best branding architecture namely Company Brand, Branded House and Endorsed Strategy Since there is a huge demand for Halal products and services coming from both Muslim and Non Muslim community, Halal Branding was introduced as they are considering Halal Branding when buying any products and services The role of social media was introduced as the moderator in the relationship between Halal brand Architecture and Social Sustainability